(untitled) (The Journal of Medicine, Humanity and Media, 2023)
Population-wide primary prevention through modifiable risk factors such as smoking, physical inactivity, and unhealthy dietary practices, has been proposed as a proactive, efficient and cost-effective method for reducing the economic burden of chronic disease worldwide. Identification of a target population’s knowledge, behaviours, and beliefs related to chronic diseases is essential for effective and appropriate chronic disease prevention. This chapter examines the findings from three research projects focusing on the cross-cultural distinction between East Indian-Canadian, Chinese-Canadian, and Mainland Chinese populations on their knowledge, behaviours, and beliefs related to ischemic heart disease or stroke. Cross-sectional descriptive comparative quantitative data analyses reveal that different mechanisms of knowledge acquisition, behaviour change, and belief transformation form the barriers to realize actual changes in those populations when primary prevention educational programs originally designed for European-Canadians were delivered without any change. Confucian teaching on the commonality of human nature and the distinction of their habits, which includes their knowledge, behaviours, and beliefs towards health, illness and disease, is reflected in the conclusion of this chapter.